Framework for the Classification of Emotions in People With Visual Disabilities Through Brain Signals - López-Hernández, Jesús Leonardo; González-Carrasco, Israel; López-Cuadrado, José Luis; Ruiz-Mezcua, Belén (Frontiers in Neuroinformatics, 2021)
Nowadays, the recognition of emotions in people with sensory disabilities still represents a challenge due to the difficulty to generalize and model the set of brain signals. In recent years, the technology that has been used to study a person's behaviour and emotions based on brain signals is the Brain-Computer Interface. Although previous works have already proposed the classification of emotions in people with sensory disabilities using machine learning techniques, a model of recognition of emotions in people with visual disabilities has not yet been evaluated. Consequently, in this work, the authors present a two-fold framework focused on people with visual disabilities. Firstly, auditory stimuli have been used, and a component of acquisition and extraction of brain signals has been defined. Secondly, analysis techniques for the modelling of emotions have been developed, and machine learning models for the classification of emotions have been defined. Based on the results, the algorithm with the best performance in the validation is Random-Forest, with an accuracy of 85% and 88% in the classification for negative and positive emotions, respectively. According to the results, the framework is able to classify positive and negative emotions, but the experimentation performed also shows that the framework performance depends on the number of features in the dataset and the quality of the EEG signals is a determining factor.